Endometrial hyperplasia – diagnosis and therapy - Obrębowska, Anna; Sajdak, Stefan (Contemporary Oncology/Współczesna Onkologia, 2000)
Endometrial hyperplasia is one of the most common causes of bleeding in perimenopausal women. The delay in diagnosis settlement and treatment introducing can lead to endometrial cancer. In this article several methods of diagnosis in endometrial pathology with particularly important hysterescopy were presented . Apart from diagnosis three different ways of treatment depending on histopathological type of hyperplasia, age and general status of the patient are shown.